Never die alone [large type] - Jackson, Lisa (Jackson, Lisa. Rick Bentz/Reuben Montoya novels., 2015)
"Detectives Bentz and Montoya are seeking a serial killer. His victims are always twins. He strikes on the cusp their twenty-first birthday, their ritualistic murders planned in exquisite detail, down to the moment when they breathe their last together"--